Internet of Things (IoT) for farming - Jeong, SangJun (Nanyang Technological University, 2022)
The food supply became a concern as we experience a recent pandemic and global supply chain disruption. To overcome similar external factors affecting the food supply and to create resilience in food security, Singapore Food Agency announced 30 by 30, to locally produce 30% of the food needs by the year 2030. This project is to develop a prototype that can be implemented for indoor farming with IoT technology. Different types of IoT protocols were covered to explore what is the most suitable for indoor farming. The advantages and disadvantages of IoT farming and the potential applications are studied for the project. The product is designed to have the data collected by the sensors, and controllers are configured to maintain the optimized plant growth condition. Real-time data collected from the plant is sent to the PC and mobile remotely by WIFI. The project is to implement various IoT functionalities to increase productivity for indoor farm management